On the Way Home: Promoting Caregiver Empowerment, Self-Efficacy, and Adolescent Stability during Family Reunification following Placements in Residential Care. Issue 4 (1st October 2020) - Trout, Alexandra L.; Lambert, Matthew C.; Thompson, Ronald; Duppong Hurley, Kristin; Tyler, Patrick
ABSTRACT: Although newly passed federal regulations mandate the provision of family-based aftercare supports for adolescents served in therapeutic residential care, very little research has been conducted to determine best practice. This efficacy and replication study compares the outcomes of youths and caregivers randomly assigned to On the Way Home (OTWH; n = 98) or traditional aftercare supports ( n = 89) following discharge from therapeutic residential care (TRC). Findings were mixed. At posttest (12-months) no significant differences were found between groups on indicators of placement stability and school involvement, however, significant differences were found between groups on several indicators of caregiver empowerment and self-efficacy, with caregivers in OTWH reporting greater levels of self-efficacy and empowerment across the domains of family and community. At follow-up (21-months), moderate to large differences were found between groups on indicators of placement stability and school involvement, with odds ratios indicating youths in OTWH were 2 and 3 times more likely to be engaged in school and living in the community, respectively. Implications, limitations, and future research are discussed.